CORRECTIVE FEEDBACK IN ENGLISH CLASS - Meirina Astia (Center of Language and Cultural Studies [CLCS], 2018)
The design of this study was classroom based observation research. The focus of this study was corrective feedback made by English teachers in the classroom. This study identified occurrences of the correction during the daily conversation course and the way teachers performed the corrective feedback in the classroom. Data were presented under the descriptive way and analyzed inductively in terms of features and facts of teacher’s teaching process (teacher’s corrective feedback). The study revealed that teacher’s corrective feedback is one factor that influences the progress of students in learning English. It did not bother the students in building a communication. The evidence showed that that the teacher applied recasts, explicit correction, and clarification requests. Recasts was dominated the type of corrective feedback used by the teacher because it did not make the students confused. Three criteria of effective corrective feedback occurred in correction given by the teacher. He was consistent in treating the errors, gave correction without breaking the flow of the communication, and did not ridicule the students in giving correction.